2015
DOI: 10.1017/jfm.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the coupling between the tumbling of rods and the velocity gradient tensor in turbulence

Abstract: We present simultaneous experimental measurements of the dynamics of anisotropic particles transported by a turbulent flow and the velocity gradient tensor of the flow surrounding them. We track both rod-shaped particles and small spherical flow tracers using stereoscopic particle tracking. By using scanned illumination, we are able to obtain a high enough seeding density of tracers to measure the full velocity gradient tensor near the rod. The alignment of rods with the vorticity and the eigenvectors of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
72
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 38 publications
10
72
1
Order By: Relevance
“…Spheroids' tendency to emphasize specific components of rotation can be explained by examining their orientation relative to fluid vorticity; the inner product between a particle's orientation vector and the local fluid vorticity vector yields an angle α, shown in Figure 2 for the nearly-isotropic channel center. For St=0 particles, results replicate previous observations [8][9][10][11][12][13][14] for discs and rods. Discs tend to align with their symmetry axis (z') orthogonal to the fluid vorticity, causing strong tumbling [8][9][10][11][12][13][14] and weak spinning [11,13].…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Spheroids' tendency to emphasize specific components of rotation can be explained by examining their orientation relative to fluid vorticity; the inner product between a particle's orientation vector and the local fluid vorticity vector yields an angle α, shown in Figure 2 for the nearly-isotropic channel center. For St=0 particles, results replicate previous observations [8][9][10][11][12][13][14] for discs and rods. Discs tend to align with their symmetry axis (z') orthogonal to the fluid vorticity, causing strong tumbling [8][9][10][11][12][13][14] and weak spinning [11,13].…”
supporting
confidence: 89%
“…For St=0 particles, results replicate previous observations [8][9][10][11][12][13][14] for discs and rods. Discs tend to align with their symmetry axis (z') orthogonal to the fluid vorticity, causing strong tumbling [8][9][10][11][12][13][14] and weak spinning [11,13]. Rods align parallel to local vorticity [8,[10][11][12][13][14] and thus spin along with it.…”
supporting
confidence: 89%
“…[7][8][9] It has been observed that disk-like particles tumble more than rod-like particles. 4,5,7,8 Rod-like particles preferentially align with the fluid vorticity vector and the vorticity component along the rod axis does not contribute to their tumbling.…”
mentioning
confidence: 99%
“…2,3,6,7 In contrast to the rod-like particles, disks align perpendicular to the fluid vorticity vector and this preferential orientation results in higher tumbling rates. 5,9 The Lagrangian fluid stretching in turbulence aligns the major axis of an anisotropic particle with the fluid vorticity. 6 The variance of the total rotation rate of a spheroidal particle is almost independent of the particle shape.…”
mentioning
confidence: 99%
“…Applications to three dimensions are less common because they are computationally expensive, rely on the accurate knowledge of the time-varying 3D velocity field that is challenging from both observational or modeling perspectives, and require advanced visualization of LCSs. As the LCS methods advance, in parallel with experimental ability to measure highly resolved 3D velocity fields [115], it is hoped that our ability to tackle three-dimensional unsteady flows will improve.…”
Section: Flow Dimensionalitymentioning
confidence: 99%